The use of modern QbD approaches in the pharmaceutical development of technology of liposomal eye drops - Kruglov, Evgen; Borshchevsky , Gennady (Annals of Mechnikov's Institute, 2022)
Introduction. Delivery of drugs to ocular tissues is of great interest, aimed at nanobiotechnological products, in particular liposomal drugs. The development of technology for the production of nanostructured drugs, which include liposomes, requires a large amount of experimental work focused on research and optimization of technological conditions, validation of processes, selection of auxiliary components. The aim of the work was to propose the technology of obtaining liposomal eye drops on the basis of experiment according to the QbD approach and to evaluate the influence of critical process parameters (CPP) on critical quality indicators (CQA) of the obtained intermediates. Materials and methods. Lipids were used to make liposomes. Value pH was monitored on a pH-meter Seven Compact (Mettler Toledo, USA). Method of high pressure extrusion, which was performed on the Microfluidiser M-110P (Microfluidics, USA) used for homogenization. The size of the liposomes was determined at 20 °C on a Zetasizer Nano ZS (Malvern Instruments, UK). The level of encapsulation of the peptide complex in liposomes, the concentration of the peptide complex, the content of impurities were monitored by high performance liquid chromatography (HPLC) using Agilent 1200 chromatographs (USA). Results and discussion. Based on statistical modeling, a flexible and reliable technology of liposomal eye drop has been developed. The optimal parameters of the technological stages of the production process have been established. All stages of the process were studied empirically and the interactions between the variable parameters of the technology were analyzed. Key factors involved in manufacturing operations were examined for risks assessment. All possible factors were identified, analyzed and evaluated. Most of the factors were either non-critical or controlled in the process. Conclusions. While developing the technological process, risks of each unit of operation were considered. Experimental studies have been identified and performed with the aim of establishing additional scientific knowledge and understanding to reduce risks to an acceptable level. Following the experiments, the initial risk assessment of the technological process has been updated. Keywords: eye drops, technology, liposome, quality. DOI: 10.5281/zenodo.6350205